TEACHERS ROLES AND PARENTAL INVOLVEMENT: IMPLEMENTATION OF 2013 CURRICULUM (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
The role of the teacher is a pivotal key in the implementation of the 2013 curriculum. Not only the teacher's roles but also parental involvement plays a supporting role to achieve the objectives of implementing the curriculum. In order, collaboration between both is very necessary. In this study conducted a qualitative research method. It involved six informants’; three English teachers and 3 parents from state, private, and religious senior high school in Makassar, South. The instruments used Semi-structured interviews. The interviews were transcribed, coded and analyzed. The main findings and components of this study included the teachers’ roles and parental involvement as an essential source of information. The teacher's role is to apply the 2013 curriculum according to the procedure Which focuses on balance in cognitive, psychomotor, and emotional aspects by integrating subjects with one another. The parental involvement that domains found in this study as followed communicating, volunteering, and learning at home.
Keywords: Teachers Roles; Parental Involvement; 2013 Curriculum